2014
DOI: 10.4238/2014.march.31.11
|View full text |Cite
|
Sign up to set email alerts
|

Homology-based cloning and expression analysis of Rf genes encoding PPR-containing proteins in tobacco

Abstract: ABSTRACT. As a model plant, mechanisms of the cytoplasmic male sterility/restoration of fertility (CMS/Rf) system in tobacco are seldom studied. Using Rf gene sequences from other Solanaceae plants and the draft genome of Nicotiana benthamiana, degenerate primers were designed to amplify the cDNA pool of N. tomentosiformis. In total, six possible Rf sequences were identified, two of which contained basedeletion mutations. The other four were intact open reading frames, of which NtomPPR5 harbored a 3-pentatrico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In this study, a CYC-B gene orthologue was successfully identified from the loquat using a homology-based cloning method, a simple, fast, and efficient method that uses highly conserved sequences to design degenerate primers to clone target genes. This has been used for carrots [34], Phalaenopsis Hybrida [35], and tobacco [36], etc.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a CYC-B gene orthologue was successfully identified from the loquat using a homology-based cloning method, a simple, fast, and efficient method that uses highly conserved sequences to design degenerate primers to clone target genes. This has been used for carrots [34], Phalaenopsis Hybrida [35], and tobacco [36], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Fertility restoration genes in N. alata were amplified using one of the degenerate Rf primer couple (Forward: 5′‐ATGACGAGAAYTTCTMTGCTKCGT‐3; Reverse: 5‐TCACT TWTTACTTCCCGAGTGAAA‐3) previously designed by Ding et al. () in N. tomentosiformis . Amplification was performed in 20 μ l volume reaction including 10 μ l of 2× Power Taq PCR Mastermix (BioTeke), 2 μ l of forward and reverse primers (10 μ m each), 2 μ l of cDNA (approximately 50 ng/ μ l) and 6 μ l of deionized water.…”
Section: Fertility Restoration Gene Cloning and Sequence Analysismentioning
confidence: 99%
“…Reverse: 5-TCACT TWTTACTTCCCGAGTGAAA-3) previously designed by Ding et al (2014) in N. tomentosiformis. Amplification was performed in 20 ll volume reaction including 10 ll of 29 Power Taq PCR Mastermix (BioTeke), 2 ll of forward and reverse primers (10 lM each), 2 ll of cDNA (approximately 50 ng/ll) and 6 ll of deionized water.…”
Section: Fertility Restoration Gene Cloning and Sequence Analysismentioning
confidence: 99%
See 2 more Smart Citations